2017
DOI: 10.1002/ijc.30548
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the tumor size at cure threshold among aggressive non-small cell lung cancers (NSCLCs): evidence from the surveillance, epidemiology, and end results (SEER) program and the national lung screening trial (NLST)

Abstract: The National Lung Screening Trial (NLST) demonstrated that non-small cell lung cancer (NSCLC) mortality can be reduced by a program of annual CT screening in high-risk individuals. However, CT screening regimens and adherence vary, potentially impacting the lung cancer mortality benefit. We defined the NSCLC cure threshold as the maximum tumor size at which a given NSCLC would be curable due to early detection. We obtained data from 518,234 NSCLCs documented in the U.S. SEER cancer registry between 1988 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In the present study, we also noted that the lung cancer in females had a better prognosis, which is consistent with previous studies. [18][19][20] In addition, we found the patients with the main bronchus as the primary tumor site and liver metastasis had a worse prognosis, which is also consistent with previous studies. 21,22 Moreover, SCLC has been widely recognized with high malignancy and early extensive brain metastases in lung cancer, and reduced responsiveness to therapy.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we also noted that the lung cancer in females had a better prognosis, which is consistent with previous studies. [18][19][20] In addition, we found the patients with the main bronchus as the primary tumor site and liver metastasis had a worse prognosis, which is also consistent with previous studies. 21,22 Moreover, SCLC has been widely recognized with high malignancy and early extensive brain metastases in lung cancer, and reduced responsiveness to therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Hattori reported 10.6% of nodal involvement and 15.1% of recurrence in the subcentimeter pure-solid NSCLC ( 9 ), which indicates that radiological solid lesions with a size of ≤1 cm should be positively treated, regardless of their small size. Goldwasser reported that 32.1% of male and 24.2% of female NSCLC patients were found to have distant metastatic disease with diameter of primary site ≤15 mm ( 36 ). He then established a mathematical model to estimate the tumor size at cure threshold based on the SEER database, and a size of 5–15 mm was recommended for intervention before progression to an incurable disease ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Goldwasser reported that 32.1% of male and 24.2% of female NSCLC patients were found to have distant metastatic disease with diameter of primary site ≤15 mm ( 36 ). He then established a mathematical model to estimate the tumor size at cure threshold based on the SEER database, and a size of 5–15 mm was recommended for intervention before progression to an incurable disease ( 36 ). From a prospective standpoint, we suggest that both indication and eligibility for surgery should be actively evaluated for nodules ≤8 mm, especially for those with a high pretest probability of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…9 Meanwhile, the fact that the majority of nonsmall cell lung cancers (NSCLCs) in the NLST were treated when they were greater in size than the curable threshold poses a diagnostic and management challenge. 10 There is a need for early, precise detection tools to identify malignant tumors at smaller sizes within the curable threshold in order to apply LDCT to maximize the benefits of lung cancer screening.…”
Section: Introductionmentioning
confidence: 99%